Application of sulfidation conditioning agents in the recovery of valuable metals from copper slag

By using vulcanization and reducing reaction in copper slag, the problems of single and secondary pollution of valuable metal types in the prior art are solved, and the synchronous efficient recovery of copper, lead, zinc and iron and gypsum slag are achieved. Resource processing.

CN118813968BActive Publication Date: 2025-02-07CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411292671.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-02-07
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

The prior art has a single type of valuable metal recovered from copper slag and there is a problem of secondary pollution.

Method used

Using vulcanized tempering agents, including gypsum slag, carbonaceous reducing agent and sodium sulfate waste salt, the metal oxides in the copper smelting slag are converted into metal sulfides through vulcanization reduction reaction, achieving the synchronization of copper, lead, zinc and iron. Recycle.

Benefits of technology

The step-by-step recycling of valuable metals in copper smelting slag was achieved, pollution was reduced, the latent heat of copper slag was utilized, and the resource treatment of gypsum slag was achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118813968B_ABST
    Figure CN118813968B_ABST
Patent Text Reader

Abstract

The present invention provides an application of a sulfurization conditioning agent in recovering valuable metals in copper slag, wherein the sulfurization conditioning agent comprises gypsum slag, a carbonaceous reducing agent and / or sodium sulfate waste salt; the composition of the carbonaceous reducing agent comprises fixed carbon, the composition of the gypsum slag comprises calcium sulfate, and the mass ratio of the gypsum slag to the carbonaceous reducing agent in the sulfurization conditioning agent is 2 to 4:1. The sulfurization conditioning agent in the present invention is composited with solid waste, and can be used to treat copper slag to efficiently achieve the enrichment and separation of valuable metals, has excellent environmental and economic benefits, and has great prospects for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of slag treatment, and in particular to the application of a sulfiding conditioning agent in recovering valuable metals in copper slag. Background Art

[0002] Copper slag is the product of the pyrometallurgical copper-nickel-cobalt smelting process. Every ton of refined copper produced produces about 2 to 3 tons of copper slag. The storage of a large amount of copper slag requires the occupation of land or farmland. Its composition is complex and causes varying degrees of pollution to the surrounding environment. However, copper slag contains a large amount of usable resources.

[0003] The current resource utilization of copper slag is mainly based on mineral processing to recover valuable metals and the utilization of tailings as cement and building materials. However, with the promotion and application of modern oxygen-enriched enhanced smelting technology in the copper smelting process, the proportion of valuable metals lost in the oxidized state dissolved in silicates in the smelting slag has increased significantly, while traditional flotation can only have a significant recovery effect on mechanically included copper sulfide particles, and cannot simultaneously recover oxidized copper. At the same time, in the existing copper mineral resources, heavy metals such as lead, zinc and iron often coexist, and are impurities in the copper smelting process and are generally removed in the smelting slag. The existing copper slag recovery does not pay attention to the recovery of lead, zinc and iron, resulting in a waste of lead, zinc and iron resources.

[0004] In order to recover valuable metals from copper smelting slag, the industry currently mainly uses flotation, reduction smelting and reduction sulfidation smelting methods to recover valuable metals. In the prior art, sulfuric acid-containing materials are mixed with copper smelting slag for low-temperature roasting, and then iron, copper and zinc metal elements are recovered by water leaching. The iron element can be effectively recovered, but a large amount of leaching liquid and acidic waste residue are generated in the process, which is difficult to handle and causes secondary pollution. Or only a single valuable metal can be recovered from the copper slag, and copper, lead, zinc and iron cannot be recovered simultaneously. Summary of the invention

[0005] The main purpose of the present invention is to provide an application of a sulfurized conditioning agent in recovering valuable metals in copper slag, aiming to solve the problems of single type of valuable metals recovered from copper slag in the prior art and secondary pollution.

[0006] To achieve the above object, the present invention provides a sulfurization conditioning agent, which comprises gypsum slag, a carbonaceous reducing agent and / or sodium sulfate waste salt;

[0007] The carbonaceous reducing agent comprises fixed carbon, the gypsum slag comprises calcium sulfate, and the molar ratio of the fixed carbon to the calcium sulfate in the sulfurization conditioning agent is 2-5:1.

[0008] Furthermore, when the sulfurization conditioning agent is composed of gypsum slag and a carbonaceous reducing agent, the mass ratio of the gypsum slag to the carbonaceous reducing agent is 2 to 4:1;

[0009] When the sulfurization conditioning agent is composed of gypsum slag, carbonaceous reducing agent and sodium sulfate waste salt, the mass ratio of the gypsum slag, carbonaceous reducing agent and sodium sulfate waste salt is 0.1~2:1:2~6.

[0010] Furthermore, the vulcanization conditioning agent is in the form of tablets or particles with a size of 0.1 to 10 mm.

[0011] Furthermore, the carbonaceous reducing agent includes one or more of coke, waste carbon material and pulverized coal, and the gypsum slag includes desulfurization gypsum in a smelter and / or neutralizing gypsum in wastewater.

[0012] The present invention also provides a use of the sulfiding conditioning agent as described in any one of the above items in recovering valuable metals in copper slag, wherein when the slag of the pyrometallurgical copper smelting process is in a hot state, the sulfiding conditioning agent is added thereto and the slag is slowly cooled to room temperature to obtain slowly cooled slag; wherein the slag includes copper slag;

[0013] The sulfur content of the sulfurizing conditioning agent is 1 to 3 times the theoretical sulfur content required to sulfide all the metal oxides in the slag into metal sulfides;

[0014] The slowly cooled slag is subjected to grinding treatment and flotation treatment in sequence to obtain metal sulfides, alloys and / or zinc ferrite; wherein the metal sulfides include sulfides of copper, lead, zinc and iron.

[0015] Furthermore, the copper grade in the copper slag is 0-4%, and the iron grade is 0-50%; in terms of mass fraction, the chemical composition (wt%) of the copper slag is: Fe 20-50, Cu 0.2-5.0, Pb 0.3-3.0, Zn 1.0-5.0.

[0016] Furthermore, the amount of the sulfurizing conditioning agent added is 3% to 20% of the mass of the slag.

[0017] Furthermore, the slow cooling rate is 1-3°C / min.

[0018] Furthermore, the grinding treatment step includes: the slow cooling slag is subjected to coarse crushing, fine crushing, and ball milling to control the particle size within a range of -80 to -200 meshes; the flotation treatment step includes: adding a flotation agent to the slowly cooling slag after grinding to allow the matte particles to sink to the bottom, thereby separating the matte from the slag.

[0019] The beneficial effects achieved by the present invention are:

[0020] The present invention provides a sulfurization conditioning agent, which combines gypsum slag, sodium sulfate waste salt and / or carbonaceous reducing agent to carry out sulfurization reduction of metal oxides in copper slag, so that lead, zinc and copper are enriched in the form of metal matte and alloy, and zinc and iron are mainly enriched in the form of zinc ferrite, so as to finally realize the step-by-step recovery of valuable metals in copper smelting slag, and at the same time realize the resource treatment of gypsum slag by treating waste with waste. The method is simple to operate, has efficient reaction, and can use the latent heat of copper slag to quickly realize the resource utilization, reduction and harmlessness of copper smelting slag and gypsum slag.

[0021] The specific sulfurization-reduction reaction occurring in the present invention includes:

[0022] The oxidized valuable metals (MeO) in copper smelting slag react with CaSO4 in gypsum solid waste and Na2SO4 in waste sodium sulfate to produce valuable metal sulfides [MeS]:

[0023] (MeO)+CaSO4+4C=[MeS]+(CaO)+4CO(g)

[0024] (MeO)+CaSO4+4CO(g)=[MeS]+(CaO)+4CO2(g)

[0025] Na2SO4+2C=Na2S+2CO2(g)

[0026] (MeO)+Na2S=[MeS]+Na2O

[0027] As the reaction temperature of the material continues to increase, sulfate [MeSO4] will continue to decompose in a reducing atmosphere to generate the corresponding metal sulfide [MeS]:

[0028] [MeSO4]+4C=[MeS]+4CO(g)

[0029] [MeSO4]+2CO(g)=[MeS]+2CO2(g)

[0030] Metal sulfides Copper sulfide oxide:

[0031] [MeS]+CuO=[CuS]+MeO

[0032] Iron oxides and silicates in copper smelting slag will also be reduced and sulfided to [FeS], and further sulfided metal oxides in the slag:

[0033] (MeO)+[FeS]=[MeS]+(FeO)

[0034] Under a strong reducing atmosphere, the metal oxides (MeO) in the smelting slag will also be reduced to metal elements and enter the matte phase:

[0035] (MeO)+C=[Me]+CO(g)

[0036] (MeO) + CO(g) = [Me] + CO2(g) BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0038] Figure 1 This is a physical picture of the slow-cooling slag sample obtained in Example 1 of the present invention;

[0039] Figure 2 is the XRD pattern of the slowly cooled slag sample prepared in Example 1 of the present invention;

[0040] Figure 3 This is a SEM image of the slowly cooled slag sample prepared in Example 1 of the present invention;

[0041] Figure 4 This is a physical picture of the slow-cooling slag sample prepared in Example 2 of the present invention;

[0042] Figure 5 is the XRD pattern of the slowly cooled slag sample prepared in Example 2 of the present invention;

[0043] Figure 6 : is a SEM image of the slow-cooling slag sample prepared in Example 2 of the present invention; wherein, Figure a is an electron microscope image of the slow-cooling slag, Figure b is a backscattering surface scan image of the slow-cooling slag, Figure c is a schematic diagram of the distribution of iron elements in the slow-cooling slag under an electron microscope, Figure d is a schematic diagram of the distribution of sulfur elements in the slow-cooling slag under an electron microscope, Figure e is a schematic diagram of the distribution of oxygen elements in the slow-cooling slag under an electron microscope, Figure f is a schematic diagram of the distribution of lead elements in the slow-cooling slag under an electron microscope, Figure g is a schematic diagram of the distribution of calcium elements in the slow-cooling slag under an electron microscope, and Figure h is a schematic diagram of the distribution of copper elements in the slow-cooling slag under an electron microscope;

[0044] Figure 7 This is a physical picture of the slow-cooling slag sample prepared in Example 3 of the present invention;

[0045] Figure 8 is the XRD pattern of the slowly cooled slag sample prepared in Example 3 of the present invention;

[0046] Fig. 9 This is a SEM image of the slowly cooled slag sample prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] It should be noted that, in the absence of conflict, the following embodiments and features in the embodiments can be combined with each other. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments rather than to limit the scope of protection of the present invention.

[0049] Unless otherwise defined, all technical and scientific terms used in the present invention are consistent with the prior art knowledge of those skilled in the art and the description of the present invention. The present invention can also be implemented using any methods, devices and materials in the prior art that are similar or equivalent to the methods, devices and materials described in the embodiments of the present invention.

[0050] When the embodiments give numerical ranges, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. The test methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers. The materials or reagents required in the following embodiments are commercially available unless otherwise specified.

[0051] In order to solve the problems of single type of valuable metals recovered from copper slag in the prior art and secondary pollution, the present invention provides a sulfiding conditioning agent, which includes gypsum slag, sodium sulfate waste salt and a carbonaceous reducing agent.

[0052] The sulfurization conditioning agent provided by the present invention is composed of solid wastes such as gypsum slag, sodium sulfate waste salt and / or carbonaceous reducing agent, thereby achieving efficient utilization of solid wastes.

[0053] For example, the sulfurization conditioning agent may consist of gypsum slag and a carbonaceous reducing agent.

[0054] Specifically, the mass ratio of gypsum slag to carbonaceous reducing agent can be 2-4:1.

[0055] In some embodiments, the sulfurization conditioning agent can be prepared by mixing gypsum slag and a carbonaceous reducing agent in a mass ratio of 2 to 4:1, and then performing tableting or granulation to obtain the sulfurization conditioning agent; wherein the size of the sulfurization conditioning agent can be 0.1 to 10 mm, and the sulfurization conditioning agent of this size can fully contact with the hot copper slag, thereby accelerating mass transfer and fully reacting.

[0056] Exemplarily, the gypsum slag includes desulfurized gypsum in a smelter and / or neutralized gypsum in wastewater, wherein the desulfurized gypsum slag is mainly composed of CaSO4·xH2O.

[0057] Calculated by mass fraction, the chemical composition of gypsum slag can be Ca 25.0%~30.0%, Mg 0.45%~0.50%, K0.03%~0.035%, Fe 0.10%~0.15%, Cd 0.010%~0.015%, Cu 0.0003%~0.0006%, S 17.00%~20.00%, and Pb 0.010%~0.013%.

[0058] Also illustratively, the carbonaceous reducing agent includes one or more of coke, waste carbon material and pulverized coal.

[0059] In terms of mass fraction, the chemical composition of the carbonaceous reducing agent may be (wt%): C 80%~85%, H 5%~10%, S 2%~4%, N 1%~3%.

[0060] As another example, the sulfurization conditioning agent may be composed of gypsum slag, a carbonaceous reducing agent, and sodium sulfate waste salt.

[0061] Specifically, the mass ratio of gypsum slag, carbonaceous reducing agent and sodium sulfate waste salt can be 0.1~2:1:2~6.

[0062] The present invention also provides a use of any of the above-mentioned sulfiding conditioning agents in recovering valuable metals in copper slag, comprising the steps of:

[0063] S1. When the slag of the pyrometallurgical copper smelting process is in a hot state, a sulfiding conditioning agent is added thereto and the slag is slowly cooled to room temperature to obtain slowly cooled slag; wherein the slag includes copper slag.

[0064] Specifically, the physical phases of copper slag are mainly composed of bornite, chalcocite, metallic copper, magnetite, fayalite, amorphous phase substances and other aggregates, and the chemical composition (wt%) and mass percentage are Fe 20~50, Cu 0.2~5.0, Pb 0.5~3.0, and Zn1.0~5.0.

[0065] Exemplarily, the copper grade in the copper slag is 0-10%, and the iron grade is 0-50%.

[0066] The sulfidation conditioning agent can be added into the flowing hot copper slag from the feeding port on the side of the chute, and most of the sulfidation conditioning agent is immersed in the hot copper slag, further ensuring the full contact between the two, so that the reduction sulfidation reaction can be carried out efficiently and fully. The temperature of the hot copper slag can be 1150-1350°C.

[0067] In some embodiments, the sulfur content in the sulfurizing conditioning agent is 1 to 3 times the theoretical sulfur content required to sulfide all the metal oxides in the slag into sulfides.

[0068] In other embodiments, the amount of the sulfurizing conditioning agent added is 3% to 20% of the mass of the slag.

[0069] The sulfidation conditioning agent is a compound of gypsum slag, waste carbon material (aluminum electrolysis process) or coke powder and sodium sulfate waste salt mixed in a certain proportion as a by-product of the metallurgical process. Specifically, the molar ratio of fixed carbon to calcium sulfate in the sulfidation conditioning agent is 2~5:1. With the help of calcium and sulfur components in gypsum slag and sodium and sulfur components in waste salt, the copper, lead and zinc components in the copper slag are synergistically sulfided and converted into metal matte particles under a slightly reducing atmosphere. The matte particles continue to aggregate and grow during the slow cooling process, reaching the particle size requirement (>40μm) that is conducive to subsequent grinding-flotation.

[0070] S2. The slowly cooled slag is subjected to grinding treatment and flotation treatment in sequence to obtain metal sulfides, alloys and / or zinc ferrite; wherein the metal sulfides include sulfides of copper, lead, zinc and iron.

[0071] The metal matte is separated from the silicate copper slag after slow cooling to form a single metal matte ore phase, and then the valuable metals such as lead, zinc and copper are recovered through the grinding-flotation process. The recovered metal matte / alloy (sulfides and alloys such as copper, lead, zinc and iron) are sent to the next step of blowing for further recovery.

[0072] It should be noted that slow-cooling slag is a general solid waste. After further recovery of elements such as lead, zinc, copper and iron, it can be sold as raw materials for cement and building materials, which meets the requirements of green and clean development of the metallurgical industry.

[0073] That is, the sulfiding conditioning agent provided by the present invention is applied to the recovery of valuable metals in copper slag. It is only necessary to add the sulfiding conditioning agent to the slag of the pyrometallurgical copper smelting process when it is in a hot state, and slowly cool the slag to room temperature. The metal sulfide particles will continuously aggregate and grow during the slow cooling process, reaching a particle size requirement (>40 μm) that is beneficial to subsequent grinding-flotation. Then, grinding treatment and flotation treatment are sequentially performed to obtain metal matte (including sulfides of copper, lead, zinc, and iron), alloys and / or zinc ferrite.

[0074] The recovery process of valuable metals in copper slag is simple to operate, highly efficient, and can treat waste with waste, achieving the simultaneous and efficient recovery of copper, lead, zinc, and iron in copper slag, while achieving the harmlessness, reduction, and resource utilization of desulfurized gypsum slag and non-ferrous smelting slag, solving the problem of environmental pollution caused by non-ferrous smelting slag; and it will not cause pollution. It is suitable for industrial promotion and has broad application prospects.

[0075] At the same time, the heavy metal elements in the above hazardous wastes are transformed into the silicate lattice in the slow-cooling copper slag during the slow-cooling process and are stabilized.

[0076] The specific sulfurization-reduction reaction occurring in the present invention includes:

[0077] The oxidized valuable metals (MeO) in copper smelting slag react with CaSO4 in gypsum solid waste and Na2SO4 in waste sodium sulfate to produce valuable metal sulfides [MeS]:

[0078] (MeO)+CaSO4+4C=[MeS]+(CaO)+4CO(g)

[0079] (MeO)+CaSO4+4CO(g)=[MeS]+(CaO)+4CO2(g)

[0080] Na2SO4+2C=Na2S+2CO2(g)

[0081] (MeO)+Na2S=[MeS]+Na2O

[0082] As the reaction temperature of the material continues to increase, sulfate [MeSO4] will continue to decompose in a reducing atmosphere to generate the corresponding metal sulfide [MeS]:

[0083] [MeSO4]+4C=[MeS]+4CO(g)

[0084] [MeSO4]+2CO(g)=[MeS]+2CO2(g)

[0085] Metal sulfides Copper sulfide oxide:

[0086] [MeS]+CuO=[CuS]+MeO

[0087] Iron oxides and silicates in copper smelting slag will also be reduced and sulfided to [FeS], and further sulfided metal oxides in the slag:

[0088] (MeO)+[FeS]=[MeS]+(FeO)

[0089] Under a strong reducing atmosphere, the metal oxides (MeO) in the smelting slag will also be reduced to metal elements and enter the matte phase:

[0090] (MeO)+C=[Me]+CO(g)

[0091] (MeO) + CO(g) = [Me] + CO2(g)

[0092] In some embodiments, the rate of slowly cooling the hot slag to room temperature may be 1-3° C. / min.

[0093] Furthermore, the grinding treatment steps include coarse crushing, fine crushing, and ball milling of the copper slag to -80 to -200 mesh.

[0094] Furthermore, the flotation treatment step includes adding flotation reagents to the copper slag after grinding to make the matte particles sink to the bottom and separate the matte from the slag.

[0095] In some specific embodiments, the steps may include:

[0096] (1) mixing the gypsum slag and the coke in a certain proportion and evenly briquetting or granulating them into a sulfurization conditioning agent;

[0097] (2) adding the sulfurization conditioning agent into the flowing hot slag through the feeding port above or on the side of the chute;

[0098] (3) Slowly cool the sulfurized conditioning agent along with the slag to room temperature;

[0099] (4) The enriched material at the bottom of the slowly cooled slag is separated from the slag and crushed and finely ground together with the unsettled copper, iron, lead and zinc sulfide particles in the middle and upper parts, and then recovered by sulfide flotation. The recovered metal matte / alloy (sulfides and alloys such as copper, lead, zinc and iron) is sent to the next step of blowing for further recovery, and the slag flotation tailings are further washed to recover zinc ferrite and magnetite.

[0100] For further understanding of the present invention, examples are given below:

[0101] Example 1

[0102] Gypsum slag and coke were mixed in a mass ratio of 4:1. The chemical composition (wt%) of gypsum slag was: Ca 28.0, Mg 0.49, K 0.033, Fe 0.11, Cd 0.010, Cu 0.0005, S 19.00, Pb 0.011; the chemical composition (wt%) of coke was: C 84.00, H 5.11, S 2.85, N 1.32. Grind and mix thoroughly with an agate mortar to form a sulfide conditioning agent; 100g of bottom-blown copper slag from a smelter was taken, and the chemical composition (wt%) of the smelting slag was: Fe 40.13, Cu 3.25, Pb 1.03, Zn 3.65, Ca 2.61, Si 11.59. The mixture was put into an agate mortar and ground with 10 g of the above-mentioned sulfurization conditioning agent to mix evenly, and then put into a muffle furnace and heated to 1300°C with the furnace, kept warm for 1 hour, and cooled to room temperature at a cooling rate of 1.0°C / min to obtain slowly cooled slag.

[0103] The slow cooling slag sample obtained in this embodiment is as follows Figure 1 As shown, Figure 2The XRD test results of the slow-cooling slag sample show that the main phases of the hot copper slag after slow cooling are ferrous silicate and ferroferric oxide, and the main component of the matte phase is Cu 39 S 28 , FeS, Fe3S4, ZnS and other sulfides. The above substances can be effectively recovered in the subsequent mineral processing stage.

[0104] Figure 3 This is a SEM picture of the slow cooling slag. The test results show that 90% of the particle sizes of Cu-Fe-S matte particles and Fe-S sulfides are greater than 100μm, which can be efficiently recovered in the grinding and flotation of sulfides; at the same time, there is a clear boundary between the above sulfides and the Fe-O-Si-Ca slag phase, which is conducive to the dissociation of mineral monomers. It is calculated that the enrichment rate of copper, lead and zinc in sulfides is greater than 92%.

[0105] Example 2

[0106] Gypsum slag and coke are mixed in a mass ratio of 2:1. The chemical composition (wt%) of gypsum slag is: Ca 28.0, Mg 0.49, K 0.033, Fe 0.11, Cd 0.010, Cu 0.0005, S 19.00, Pb 0.011; the chemical composition (wt%) of coke is: C 84.00, H 5.11, S 2.85, N 1.32. Grind and mix thoroughly with an agate mortar to form a sulfide conditioning agent; take 100g of bottom-blown copper smelting slag from a smelter in Shandong, the chemical composition (wt%) of the smelting slag is: Fe 40.13, Cu 3.25, Pb 1.03, Zn 3.65, Ca 2.61, Si 11.59, put it into an agate mortar and grind and mix evenly with 10g of the above-mentioned sulfide conditioning agent, put it into a muffle furnace and heat it to 1300℃ with the furnace, keep it warm for 1h, maintain the cooling rate at 1.0℃ / min, and cool it to room temperature to obtain slow-cooling slag.

[0107] The slow cooling slag sample obtained in this embodiment is as follows Figure 4 As shown, Figure 5 This is the XRD test diagram of the slow cooling slag sample. It can be seen that the main phases obtained after the hot copper slag is slowly cooled are ferrous silicate and ferroferric oxide, and the main component of the matte phase is Cu 39 S 28 , FeS, Fe3S4, ZnS and other sulfides. The above substances can be effectively recovered in the subsequent mineral processing stage.

[0108] Figure 6The SEM image test results show that the particle size of Cu-Fe-S matte particles and Fe-S sulfide is greater than 100μm, which can be efficiently recovered in sulfide flotation; at the same time, there is a clear boundary between the above sulfide and Fe-O-Si-Ca slag phase, which is conducive to the dissociation of mineral monomers. Specifically, Figure a is a real electron microscope image of the slow cooling slag, and it can be seen that there is a clear boundary between the upper and lower layers. Figures c and e show that the upper slag phase is mainly composed of iron oxide and ferroferric oxide. Combined with Figures c, d, f, and h, it can be seen that copper, iron, and lead are enriched at the bottom in the form of sulfides, with a size greater than 1000um, and there is a clear boundary with the slag phase, which can achieve flotation separation. The enrichment rate of copper and lead in the slag is 90%.

[0109] Example 3

[0110] Gypsum slag and coke are mixed in a mass ratio of 2:1. The chemical composition (wt%) of the gypsum slag is: Ca 28.0, Mg 0.49, K 0.033, Fe 0.11, Cd 0.010, Cu 0.0005, S 19.00, Pb 0.011; the chemical composition (wt%) of the coke is: C 84.00, H 5.11, S 2.85, N 1.32. Grind and mix thoroughly with an agate mortar to form a sulfurized conditioning agent; take 100g of slow-cooled slag from a smelter in Shandong, the chemical composition (wt%) of the smelting slag is: Fe 40.13, Cu 3.25, Pb 1.03, Zn 3.65, Ca 2.61, Si 11.59, put it into an agate mortar and grind and mix evenly with 20g of the above-mentioned sulfurized conditioning agent, put it into a muffle furnace and heat it to 1300℃ with the furnace, keep it warm for 1h, maintain the cooling rate at 1.0℃ / min, and cool it to room temperature to obtain slow-cooled slag.

[0111] The slow cooling slag sample obtained in this embodiment is as follows Figure 7 As shown, Figure 8 The XRD test results of the slow cooling slag show that the main phases of the hot copper slag after melting and slow cooling are ferrous silicate and ferroferric oxide. The main components of the matte phase are Cu 39 S 28 , FeS, Fe3S4, ZnS and other sulfides. The above substances can be effectively recovered in the subsequent mineral processing stage.

[0112] Fig. 9 The SEM images in the test results show that the particle size of Cu-Fe-Pb-S matte particles and Fe-S sulfides are greater than 50μm and can be efficiently recovered in sulfide flotation; at the same time, there is a clear boundary between the above sulfides and the Fe-O-Si-Ca slag phase, which is conducive to the dissociation of mineral monomers. The copper and lead enrichment rate in the slag is 91%.

[0113] To sum up, the above technical solutions of the present invention are only preferred embodiments of the present invention, and the scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the protection scope of the present invention.

Claims

1. Application of a sulfiding conditioning agent in recovering valuable metals in copper slag, characterized in that: When the slag of the pyrometallurgical copper smelting process is in a hot state, a sulfurized conditioning agent is added thereto and the slag is slowly cooled to room temperature to obtain slowly cooled slag; The slag comprises copper slag, the sulfidation conditioning agent comprises gypsum slag, a carbonaceous reducing agent and / or sodium sulfate waste salt; the composition of the carbonaceous reducing agent comprises fixed carbon, the composition of the gypsum slag comprises calcium sulfate, the molar ratio of the fixed carbon to the calcium sulfate in the sulfidation conditioning agent is 5:1, and the chemical composition (wt%) of the copper slag is: Fe 20-50, Cu 0.2-5.0, Pb 0.3-3.0, Zn 1.0-5.0, in terms of mass fraction; The sulfur content of the sulfurizing conditioning agent is 1 to 3 times the theoretical sulfur content required to sulfide all the metal oxides in the slag into metal sulfides, and the amount of the sulfurizing conditioning agent added is 20% of the mass of the slag; The slowly cooled slag is subjected to grinding treatment and flotation treatment in sequence to obtain metal sulfides, alloys and zinc ferrite; wherein the metal sulfides include sulfides of copper, lead, zinc and iron.

2. The use of the sulfurization conditioning agent according to claim 1 in recovering valuable metals in copper slag, characterized in that: The slow cooling rate is 1-3°C / min.

3. The use of the sulfurization conditioning agent according to claim 1 in recovering valuable metals in copper slag, characterized in that: The grinding treatment step includes: the slow cooling slag is subjected to coarse crushing, fine crushing and ball milling to control the particle size within -80 to -200 mesh; the flotation treatment step includes: adding flotation reagents to the slowly cooling slag after grinding to make the matte particles sink to the bottom and separate the matte from the slag.

4. The use of the sulfurization conditioning agent according to claim 1 in recovering valuable metals in copper slag, characterized in that: When the sulfurization conditioning agent is composed of gypsum slag, carbonaceous reducing agent and sodium sulfate waste salt, the mass ratio of gypsum slag, carbonaceous reducing agent and sodium sulfate waste salt is 0.1~2:1:2~6.

5. The use of the sulfurization conditioning agent according to claim 1 in recovering valuable metals in copper slag, characterized in that: The vulcanization conditioning agent is in the form of tablets or particles with a size of 0.1 to 10 mm.

6. The use of the sulfurization conditioning agent according to claim 1 in recovering valuable metals in copper slag, characterized in that: The carbonaceous reducing agent includes one or more of coke, waste carbon material and pulverized coal, and the gypsum slag includes desulfurized gypsum in a smelter and / or neutralized gypsum in wastewater.

Citation Information

Patent Citations

  • Method for cooperatively recycling copper slag and sodium sulfate waste residues

    CN110284004A

  • Method for strengthened recycling of valuable metals in copper smelting slag by utilizing gypsum slag

    CN111979423A